Cancer Omics in Africa: Present and Prospects - El Jaddaoui, Islam; Allali, Imane; Sehli, Sofia; Ouldim, Karim; Hamdi, Salsabil; Al Idrissi, Najib; Nejjari, Chakib; Amzazi, Saaïd; Bakri, Youssef; Ghazal, Hassan (Frontiers in Oncology, 2020)
During the last century, cancer biology has been arguably one of the most investigated research ﬁelds. To gain deeper insight into cancer mechanisms, scientists have been attempting to integrate multi omics data in cancer research. Cancer genomics, transcriptomics, metabolomics, proteomics and metagenomics are the main multi omics strategies used currently in the diagnosis, prognosis, treatment and biomarker discovery in cancer. In this review, we focused on the applications of different multi omics approaches in cancer research in the African continent and discussed the main challenges facing the implementation of these approaches in African countries.